MYC regulates ductal-neuroendocrine lineage plasticity in pancreatic ductal adenocarcinoma associated with poor outcome and chemoresistance. Issue 1 (December 2017) - Farrell, Amy; Joly, Meghan; Allen-Petersen, Brittany; Worth, Patrick; Lanciault, Christian; Sauer, David; Link, Jason; Pelz, Carl; Heiser, Laura; Morton, Jennifer; Muthalagu, Nathiya; Hoffman, Megan; et al.
Abstract Intratumoral phenotypic heterogeneity has been described in many tumor types, where it can contribute to drug resistance and disease recurrence. We analyzed ductal and neuroendocrine markers in pancreatic ductal adenocarcinoma, revealing heterogeneous expression of the neuroendocrine marker Synaptophysin within ductal lesions. Higher percentages of Cytokeratin-Synaptophysin dual positive tumor cells correlate with shortened disease-free survival. We observe similar lineage marker heterogeneity in mouse models of pancreatic ductal adenocarcinoma, where lineage tracing indicates that Cytokeratin-Synaptophysin dual positive cells arise from the exocrine compartment. Mechanistically, MYC binding is enriched at neuroendocrine genes in mouse tumor cells and loss of MYC reduces ductal-neuroendocrine lineage heterogeneity, while deregulated MYC expression in KRAS mutant mice increases this phenotype. Neuroendocrine marker expression is associated with chemoresistance and reducing MYC levels decreases gemcitabine-induced neuroendocrine marker expression and increases chemosensitivity. Altogether, we demonstrate that MYC facilitates ductal-neuroendocrine lineage plasticity in pancreatic ductal adenocarcinoma, contributing to poor survival and chemoresistance. Neuroendocrine differentiation of epithelial tumor cells can contribute to cancer cell resistance and survival. Here, the authors show that dysregulated c-Myc promotes neuroendocrine differentiation in pancreatic ductal adenocarcinoma, leading to poor survival and chemoresistance.